2013
DOI: 10.1007/s11738-013-1410-y
|View full text |Cite
|
Sign up to set email alerts
|

Function of the photosynthetic apparatus of oilseed winter rape under elicitation by Phoma lingam phytotoxins in relation to carotenoid and phenolic levels

Abstract: Stem canker (blackleg) caused by fungus Leptosphaeria maculans/L. biglobosa is one of the most damaging diseases of oilseed winter rape crops. Some winter oilseed rape varieties (Brassica napus L. var. oleifera 'Bojan', 'Lisek', 'Liclassic') that differ in blackleg resistance have been chosen for the experiment. In all tested cultivars during growth on a medium with a fungal elicitor, a distinct reduction in the length of the stems, the roots and the entire length of the seedlings was observed. However, only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In the previous work we showed higher activity of the photosynthetic apparatus in 'Liclassic' plants inoculated with L. maculans spores, as compared to 'Bojan' cultivar [23]. This was also manifested in greater biomass production in 'Liclassic' seedlings.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In the previous work we showed higher activity of the photosynthetic apparatus in 'Liclassic' plants inoculated with L. maculans spores, as compared to 'Bojan' cultivar [23]. This was also manifested in greater biomass production in 'Liclassic' seedlings.…”
Section: Discussionmentioning
confidence: 63%
“…The division of winter rape cultivars in terms of susceptibility to L. maculans infection was based on field trials carried out in Polish conditions, breeding observations and our own experiments, whose results have been partly published [23]. The seeds were obtained from the Plant Breeding Center Strzelce Sp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brassicaceae, phenolics and GLS are enhanced under biotic stress . The mechanisms involved in such a response have been related to jasmonic acid (JA) .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a biotic stress this may yield additional information on the functioning of the photosynthetic apparatus at the point of inoculation with a fungal pathogen as well as in the immediate vicinity of the inoculated tissue before the first symptoms of the disease become visible (Lai et al, 2011 (Jędryczka, 2007). In our previous study we demonstrated differences in photosynthetic apparatus activity in winter rape seedlings grown on agar medium containing toxic culture of Phoma lingam filtrates at 4, 7 and 11 days after inoculation (Hura et al, 2014). Little is known about early disturbances (between days 1 and 4 post-inoculation) of photosynthetic apparatus activity in winter rape seedlings under Phoma lingam infection.…”
Section: Introductionmentioning
confidence: 95%